The relationship between physical exercise and mobile phone addiction among Chinese college students: Testing mediation and moderation effects - Zeng, Miaolin; Chen, Siyu; Zhou, Xiangyi; Zhang, Jincheng; Chen, Xin; Sun, Jingquan (Frontiers in Psychology, 2022)
Background: During the COVID-19 pandemic, suspensions of various activities and long periods of self-isolation led to a sharp increase in inappropriate use of mobile phones, which sparked public concern about mobile phone addiction (MPA). In recent years, more and more attention has been paid to physical exercise as a protective effect of MPA. However, the relationship and its internal mechanisms underlying were still unclear. The present study tested the mediating and moderating roles of self-control, rumination, psychological distress, and loneliness between physical exercise and MPA. Methods: In this cross-sectional study, the Chinese mainland was investigated by questionnaire. Primary data was collected from 1843 college students (19.75±1.3) from five universities in Sichuan Province. Mobile Phone Addiction Tendency Scale (MPATS), Physical Activity Rating Scale-3 (PARS-3), Self-Control Scale (SCS), Ruminative Response Scale (RRS), Depression Anxiety Stress Scale-21 (DASS-21) and UCLA Loneliness Scale (UCLA-20) were investigated. The mediating models were examined using SPSS PROCESS macro 3.3 software, in which the mediation variables were self-control, rumination and psychological distress, the moderation was loneliness. Gender, major and grade were included as control variables. Result: Self-control, rumination and psychological distress played a simple mediating role between physical exercise and MPA. Moreover, not only self-control and rumination, but also self-control and psychological distress played the chain mediating roles between physical exercise and MPA. The chain pathways were moderated by loneliness. Specifically, the effect was stronger among college students with higher loneliness. Conclusion: The conclusions corroborate and clarify the mechanisms that self-control, rumination and psychological distress mediated the association between physical exercise and MPA, and the mediation effects were moderated via loneliness. This present study advanced our understanding of how and when college students’ physical exercise was related to MPA. Educators and parents should pay more attention to college students’ physical exercise.